EJAAN YANG DIBENARKAN JILID 5 - Tia Agustina; Muhammad Agus Darudin; Reno; Mathyus; Ira Yunita; Lezita Malianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of digital communication technology and the widespread use of informal slang often obscure the boundary between standard and non-standard Indonesian language, causing frequent spelling errors in formal and academic writing. This study aims to examine the role, historical evolution, and implementation of Ejaan yang Dibenarkan Jilid 5 as a standardized writing guideline to maintain the clarity, quality, and credibility of written communication. This research employed a library research method with a qualitative descriptive approach, analyzing secondary sources such as official spelling manuals, linguistic textbooks, and indexed scientific journals. Data analysis was conducted through content analysis involving data reduction, data presentation, and drawing conclusions with source triangulation. The results indicate that Ejaan yang Dibenarkan Jilid 5 provides comprehensive and systematic rules covering four core domains: letter usage, word formation, punctuation, and loanword absorption. Proper application of these rules significantly enhances academic writing quality, eliminates semantic ambiguity, acts as a linguistic filter in digital interactions, and serves as a national unifying tool. To minimize persistent errors such as misapplied prefixes, non-standard terms, and missing punctuation, continuous habituation of self-editing and formal linguistic education are strongly recommended.